Embodied echoes: navigating the familiarity in continued intention to play VR game - Yang, Ling; Xiao, Daibo (Frontiers in Human Neuroscience, 2024)
IntroductionVirtual reality (VR) games, propelled by advancements in VR and artificial intelligence technologies, offer a level of realism and interactivity that traditional games cannot match. However, despite their immersive potential, VR games have not yet reached the widespread popularity of their conventional counterparts. While VR can craft the illusion of a parallel reality, users often remain cognizant of the delineation between the virtual and the real.MethodsIn this paper, we employ a blend of qualitative and quantitative research methods to explore the impact of familiarity with virtual environments and interactive elements on users sense of embodiment, flow experience, and their intention to continue playing VR games. Additionally, we examine the moderating influence of perceived cost within this framework.Results and discussionsOur analysis of 307 collected responses, facilitated by PLS-SEM, reveals that familiarity with interactivity is positively associated with both sense of embodiment and flow experience, whereas familiarity with the virtual scene primarily influences sense of embodiment. Interestingly, perceived cost exerts a positive moderating effect on the relationship between flow experience and the intention to persist with VR gaming, while it negatively moderates the impact of sense of embodiment on this intention. This study offers theoretical insights that can guide future research in the domain of VR gaming, as well as practical takeaways for companies in the VR game industry, shedding light on how to enhance user engagement and sustain long-term interest in VR gaming experiences.